Diplopia following Extraoral Maxillary Nerve Blockade for Trigeminal Neuralgia - Chavali, Siddharth; Rath, Girija P.; Bithal, Parmod K. (Journal of Neuroanaesthesiology and Critical Care, 2018)
We report a case of diplopia due to reversible abducens nerve block associated with extraoral maxillary blockade of the trigeminal nerve. This complication occurs despite precautions such as aspiration and confirmation of needle tip position with nerve stimulation. Knowledge of this condition and its potential cause should alert the physician to the importance of appropriate injection technique and an understanding of the management protocol.
Keywords: maxillary nerve block; extraoral approach; neurolytic agent; complication; abducens nerve palsy